Advanced techniques in magnetic resonance imaging of the brain in children with ADHD - Giuseppe Pastura; Paulo Mattos; Emerson Leandro Gasparetto; Alexandra Prufer de Queiroz Campos Araújo (Arquivos de Neuro-Psiquiatria, 2011)
Attention deficit hyperactivity disorder (ADHD) affects about 5% of school-aged child. Previous published works using different techniques of magnetic resonance imaging (MRI) have demonstrated that there may be some differences between the brain of people with and without this condition. This review aims at providing neurologists, pediatricians and psychiatrists an update on the differences between the brain of children with and without ADHD using advanced techniques of magnetic resonance imaging such as diffusion tensor imaging, brain volumetry and cortical thickness, spectroscopy and functional MRI. Data was obtained by a comprehensive, non-systematic review of medical literature. The regions with a greater number of abnormalities are splenium of the corpus callosum, cingulated girus, caudate nucleus, cerebellum, striatum, frontal and temporal cortices. The brain regions where abnormalities are observed in studies of diffusion tensor, volumetry, spectroscopy and cortical thickness are the same involved in neurobiological theories of ADHD coming from studies with functional magnetic resonance imaging.